2016
DOI: 10.1146/annurev-marine-122414-034058
|View full text |Cite
|
Sign up to set email alerts
|

Sources, Ages, and Alteration of Organic Matter in Estuaries

Abstract: Understanding the processes influencing the sources and fate of organic matter (OM) in estuaries is important for quantifying the contributions of carbon from land and rivers to the global carbon budget of the coastal ocean. Estuaries are sites of high OM production and processing, and understanding biogeochemical processes within these regions is key to quantifying organic carbon (Corg) budgets at the land-ocean margin. These regions provide vital ecological services, including nutrient filtration and protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(113 citation statements)
references
References 155 publications
2
93
1
4
Order By: Relevance
“…Observations over 3 years in the tidal fresh Hudson found that particulate organic carbon concentration depended more on processes in the tidal river than the external loading from tributaries, consistent with a long residence time and extensive internal processing (Findlay et al, ). Note that the sediment age calculated here represents time in the tidal river and estuary, rather than the much longer time scales for the age of organic carbon that also depend on characteristics of the aquatic, terrigenous, and anthropogenic carbon sources (Canuel & Hardison, ).…”
Section: Discussionmentioning
confidence: 99%
“…Observations over 3 years in the tidal fresh Hudson found that particulate organic carbon concentration depended more on processes in the tidal river than the external loading from tributaries, consistent with a long residence time and extensive internal processing (Findlay et al, ). Note that the sediment age calculated here represents time in the tidal river and estuary, rather than the much longer time scales for the age of organic carbon that also depend on characteristics of the aquatic, terrigenous, and anthropogenic carbon sources (Canuel & Hardison, ).…”
Section: Discussionmentioning
confidence: 99%
“…Estuaries are important zones for the production, transformation and removal of organic matter, both in dissolved and particulate form [e.g., Hedges et al ., ; Canuel and Hardison , ]. Organic matter (OM) in estuaries is derived from autochthonous (in situ production) and allochthonous (e.g., terrestrial soils and urban sewage) sources.…”
Section: Introductionmentioning
confidence: 99%
“…For the preparation of silica gel impregnated with AgNO 3 (10 wt.%), 1 g of AgNO 3 was diluted in ethanol and water and mixed with 9 g of silica gel. The solvents were rotary evaporated and the silica activated at 100 °C for 2 h. A Pasteur pipette (5 mm i.d.)…”
Section: Silica Impregnated With Agnomentioning
confidence: 99%
“…2 Algae are characterized by shorter chain lengths with no expressive odd-over-even preference. 3 In contrast, n-alkanes in fossil fuels have a wide composition range, without predominance of odd or even-numbered chains. 4 However, despite these typical fingerprints, there are cases in which n-alkane profile of different classes of organisms overlap, resulting in ambiguous interpretations of the organic material sources.…”
Section: Introductionmentioning
confidence: 99%